The Corporate Psychopaths Theory of the Global Financial Crisis - Boddy, Clive R. (2011)
This short theoretical paper elucidates a plausible theory about the Global Financial Crisis and the role of senior financial corporate directors in that crisis. The paper presents a theory of the Global Financial Crisis which argues that psychopaths working in corporations and in financial corporations, in particular, have had a major part in causing the crisis. This paper is thus a very short theoretical paper but is one that may be very important to the future of capitalism because it discusses significant ways in which Corporate Psychopaths may have acted recently, to the detriment of many. Further research into this theory is called for.
Keywords: Corporate Management; Leadership; The Global Financial Crisis; Corporate Psychopaths